Additional double-wall roof in single-wall, closed, convective incubators: Impact on body heat loss from premature infants and optimal adjustment of the incubator air temperature. Issue 9 (September 2016) - Delanaud, Stéphane; Decima, Pauline; Pelletier, Amandine; Libert, Jean-Pierre; Stephan-Blanchard, Erwan; Bach, Véronique; Tourneux, Pierre
Highlights: Preterm neonates lose heat by radiation to the cool surfaces of the incubator. A double–wall roof panel in the incubator was evaluated to reduce radiant heat loss. With an additional roof panel, radiant heat loss was lower. However, convective and evaporative skin heat losses were higher. This can be overcome by increasing the incubator air temperature (0.15–0.20°C). Abstract: Radiant heat loss is high in low-birth-weight (LBW) neonates. Double-wall or single-wall incubators with an additional double-wall roof panel that can be removed during phototherapy are used to reduce Radiant heat loss. There are no data on how the incubators should be used when this second roof panel is removed. The aim of the study was to assess the heat exchanges in LBW neonates in a single-wall incubator with and without an additional roof panel. To determine the optimal thermoneutral incubator air temperature. Influence of the additional double-wall roof was assessed by using a thermal mannequin simulating a LBW neonate. Then, we calculated the optimal incubator air temperature from a cohort of human LBW neonate in the absence of the additional roof panel. Twenty-three LBW neonates (birth weight: 750–1800 g; gestational age: 28–32 weeks) were included. With the additional roof panel, R was lower but convective and evaporative skin heat losses were greater. This difference can be overcome by increasing the incubator air temperature by 0.15–0.20 °C. The benefit of an additional roof panel was cancelled out by greater body heat losses through other routes. Understanding the heat transfers between the neonate and the environment is essential for optimizing incubators.